Heuristics: a reasoning tool in the teaching and learning of mathematics (Educational Knowledge, 2018)
The solution to a mathematical problem can be based on a series of mechanical, algorithmic, and structured procedures, which emphasize the solution method; or through the use of simple, creative, and intuitive strategies that enable divergent thinking, known as heuristics. The purpose of this article is to analyze the use of heuristic strategies as a tool for solving quantitative reasoning problems in different contexts, in order to promote the development of mathematical skills and competencies among secondary school students.
Keywords: math; heuristic; educational strategy; logical thinking; learning